Can Leaders Persuade? Examining Movement in Immigration Beliefs - Hassan Afrouzi; Carolina Arteaga; Emily Weisburst (Center for Economic Studies and ifo Institute (CESifo), 2022)
Can political leaders change constituents' beliefs? If so, is it rhetoric, identity, or the interaction of the two that matters? We construct a large-scale experiment where participants are exposed to anti-immigrant and pro-immigrant speeches from both Presidents Obama and Trump. We benchmark these treatments to versions recorded by an actor to control for speech messages. Our findings show that both leader messages and sources matter. Holding messages fixed, leaders persuade when participants hear unanticipated messages from sources perceived as reliable, consistent with a Bayesian framework. This evidence supports the hypothesis that individuals will "follow their leader" to new policy positions.
Keywords: D83; C90; 330; leaders; political beliefs; partisan identity; polarization; immigration